2014
DOI: 10.11113/jt.v69.3168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coolant Temperature on Progressive Freeze Concentration of Refined, Bleached and Deodorised Palm Oil

Abstract: This study focused on the possibility of separating refined, bleached and deodorized palm oil (RBDPO) into olein and stearin by using progressive freeze concentration (PFC) as an alternative method to replace the conventional fractionation process. PFC has the potential to be a more effective technique for olein-stearin separation, with minimal changes in the product’s quality for producing high quality edible oil. Apart from that, it requires fewer unit operations compared to conventional methods. In this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, the rate of ice crystals or solid growth is controlled by coolant temperature (Amran and Jusoh 2016 ; Jusoh et al 2014a ). When the temperature is close to the crystallization point, the likelihood of FAME being trapped is higher within the solid layer formed by glycerol and other impurities.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the rate of ice crystals or solid growth is controlled by coolant temperature (Amran and Jusoh 2016 ; Jusoh et al 2014a ). When the temperature is close to the crystallization point, the likelihood of FAME being trapped is higher within the solid layer formed by glycerol and other impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, Ding et al (2019) found that in SFC, ice crystals are suspended in a bulk solution and developed, creating a two-phase fluid of ice and mother liquor, also known as ice slurry. In general, a conventional SFC consists of three phases which are an ice nucleator, a re-crystalliser, and an ice crystal separator (Jusoh et al, 2014a).…”
Section: Suspension Freeze Concentrationmentioning
confidence: 99%